Heterogeneous ECE processes at channel electrodes: Analytical theory. Distinguishing hetero- and homogeneous ECE reactions - Aixill, W; Alden, J; Prieto, F; Waller, G; Compton, R; Rueda, M (1998)
Analytical theory is developed for heterogeneous ECE reactions occurring at channel electrodes. Simple expressions are presented that allow the ready mechanistic interpretation of experimental data and the deduction of corresponding rate constants. These are shown to be in excellent agreement with numerical simulations and consistent with experiments conducted on the reduction of nitromethane in buffered aqueous solution at Hg/Cu electrodes deposited on a platinum substrate thought to proceed via a heterogeneous ECEEE mechanism. The experimental resolution between heterogeneous and homogeneous ECE processes in general is discussed.